Ramayana connection with Walkeshwar and Banganga - Banganga by Ghosh, Ayan (2023)
The popular myth regarding how Walkeshwar got its name originate from the Ramayana. It is believed that Lord Ram and Lakshman had visited the site of Banganga during their search for Sita. They were met by rishis who suggested Rama to install a potent lingam brought from Varanasi. However, given the time it would take Lakshman to make the return journey, a shivling was made out of sand. This lingam (and the temple that later housed it) was called Walkeshwar (Walu = sand, Ishwar = God), giving the place its current name.